ANALISA VARIASI SUHU DAN WAKTU PERAWATAN TERHADAP KUAT TEKAN BETON GEOPOLIMER - Shanti Wahyuni Megasari; Fitridawati Soehardi (Program Studi Teknik Sipil FT UNS, 2025)
The increase in cement production has a negative impact on the environment, so innovation in the use of concrete adhesives is needed, one of which is by utilizing fly ash waste. In order to react to form polymer bonds, fly ash requires the addition of an activator solution in the form of Sodium Hydroxide (NaOH) and Sodium Silicate (Na2SiO3). At cold temperatures, the hydration process and initial strength of geopolymer concrete will have difficulty being achieved optimally. So additional heat with high temperatures is needed during curing to increase the compressive strength of geopolymer concrete. This study aims to analyze the temperature and curing time on the compressive strength of geopolymer concrete. The research method is an experimental study in the Laboratory with a ratio of aggregate: binder of 65%: 35%, coarse aggregate: fine aggregate of 60%: 40%, alkali: fly ash of 38%: 62%, NaOH: Na2SiO3 of 1: 2, superplasticizer 2%, and activator molarity 12 M. The variations in temperature and curing time used were at temperatures of 60 ℃ and 90 ℃ for 6 hours, 12 jams and 24 hours. Test objects in the form of cylinders measuring 200×100 mm as many as 18 samples. The test objects will be tested for compressive strength after 28 days. The results of the study obtained the highest compressive strength value at a variation of 90℃ for 24 hours of 17.92 MPa and the lowest compressive strength value at a variation of 60℃ for 6 hours of 10.19 MPa. Based on the results of the study, it was concluded that the higher the curing temperature and the longer the curing time can increase the compressive strength of geopolymer concrete. For further research, it is recommended to vary the curing temperature above 90℃, the curing time above 24 hours and reduce the amount of air in the concrete mixture. Keywords: compressive strength; curing time; fly ash; geopolymer concrete; temperature time